Reversible transition between InGaAs dot structure and InGaAsP flat surface - Ozasa, K; Aoyagi, Y; Park, YJ; Samuelson, L (AMER INST PHYSICS, 1997)
We have studied the in situ modification of coherently grown InGaAs dots by interaction with phosphorus. By monitoring the intensity of reflection high-energy electron diffraction transmission spot, the in situ phosphorus (precracked PH3) supply on the InGaAs dots was examined at 480 degrees C. It was found that the phosphorus exposure induces a surface structure change from a dot structure to a Aat surface. The change is caused by the replacement of arsenic in the dots by phosphorus, which reduces the strain between the InGaAs(P) dots and the GaAs substrate. By switching AsH3/PH3 beams in situ, a reversible transition of the surface structure between the InGaAs dot structure and the InGaAsP flat surface was observed. A transitional state between the dot structure and the hat surface was metastabilized by tuning the AsH3/PH3 beam ratio. The metastabilized surface was observed ex situ using a high-resolution scanning electron microscope. (C) 1997 American Institute of Physics.
Keywords: HIGHLY STRAINED INGAAS; INAS DOTS; EPITAXY; GROWTH; GAAS(100); ISLANDS; GAAS